Kelembagaan dan Kewenangan Hukum Ekonomi Syariah di Indonesia: Analisis Integrasi dalam Sistem Hukum Nasional - Dian May Syifa; Yamani Naufal; Ahmadi Hasan; Mujiburohman A. Abas (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The institutionalization of Sharia Economic Law in Indonesia demonstrates the state's commitment to integrating Islamic legal values into the national legal system through legislative policies, institutional development, and the allocation of authority among judicial, regulatory, and religious bodies. This development has created a distinctive legal framework that reflects the interaction between Islamic legal principles and national legal structures. An examination of this framework focuses on the legal-political foundations of Sharia Economic Law institutions, the legitimacy and distribution of authority among related institutions, and the pattern of legal integration viewed through the lenses of legal politics, institutional theory, and legal pluralism. This research adopts a normative legal method employing statutory, conceptual, and historical approaches. The analysis is based on primary legal materials consisting of legislation and supported by secondary sources derived from academic books, scholarly articles, and relevant legal literature. The findings reveal that the integration of Sharia Economic Law in Indonesia represents a model of managed legal pluralism in which Islamic legal norms acquire binding legal force after undergoing formal institutionalization by the state. Despite significant progress, several challenges persist, particularly in relation to regulatory harmonization, inter-institutional coordination, and the position of National Sharia Council-Indonesian Ulema Council (DSN-MUI) fatwas within the hierarchy of national law.